EFFICACY OF CLOPROSTENOL THERAPY IN HYDROMETRA GOATS - REDDY, K T RAMACHANDRA; KUMARI, G .ARUNA; REDDY, ANIL KUMAR; MOHAN, K MURALI; ANAND, SUNIL (The Indian Journal of Animal Reproduction, 2023)
Hydrometra is one of the causes of infertility in goats and this condition is known as pseudopregnacy ingoats. Pseudopregnancy is also observed in bitches, sow and mare. But in these animals hydrometra is notobserved in pseudopregnancy. A total of 20 hydrometra cases were diagnosed, which showed hypoechoiecfluid in the uterus on ultra sound scanning. All the cases were treated with injection Cloprostenol at the dose of250 μg each IM, twice at 1 1 - 1 2 days interval. Draining of uterine fluids was observed 2-5 days after first doseof Cloprostenol injection. 18/20 goats exhibited estrus within 2-5 days after 2 injection of Cloprostenol andout of the 1 8 estrus goats 14 become pregnant after breeding.
Keywords: Hydrometra; Pseudopreganacy; Cloprostenol; Anestrous